EVALUATION OF COST APPROACH FROM THE VIEWPOINT OF EMPLOYEES OF THE GENERAL COMPANY FOR LEATHER INDUSTRIES - THAR SAADOON SHNAISHEL; Qassim Mahal Herez; Ahmed Mohammed Hamzah (Scholar Express Journals, 2022)
The aim of the research is to evaluate the cost approaches (Target costing, Activity Based Costing, Attributes Based Costing) (Target costing, Activity Based Costing, Attributes Based Costing), by revealing the strengths and weaknesses from the viewpoint of the employees of the General Company for Leather Industries and the researcher has prepared a questionnaire consisting of (22) paragraphs that represent the common characteristics and features among the cost approaches including (cost reduction, pricing quality, competitive advantage, product quality, and raising efficiency) within a list that includes the three entries and their validity and consistency were achieved, and were applied to an intentional sample of (50) of the company’s workers and the results are : 1. The Target costing approach gets first place with (15) high strength points and (7) medium strength. 2. The Activity Based Costing approach gets the second place, with (15) high strength points and (7) medium strength. 3. The Attributes Based Costing approach is ranked third, with (13) high strength points and (9) medium strength points. There are no weaknesses for all stages. 4. The differences were significant according to the sex variable with respect to the cost approach (ABC), and were not significant for the other two variables (scientific qualification, and service in years). 5. The relationships between the cost approaches were significant and ranged between (0,479 - 0,657). The TC explained the percentage of variation in (ABC) and (ABCII). The researcher has concluded with recommendations and suggestions , most importantly to open rehabilitation studies for the workers in the company and working on the integration of three approaches.
Keywords: evaluation; costs accountancy; cost approach T.C